2008
DOI: 10.1016/j.mod.2008.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Shox2-deficiency leads to dysplasia and ankylosis of the temporomandibular joint in mice

Abstract: The temporomandibular joint (TMJ) is a unique synovial joint whose development differs from the formation of other synovial joints. Mutations have been associated with the developmental defects of the TMJ only in a few genes. In this study, we report the expression of the homeobox gene Shox2 in the cranial neural crest derived mesenchymal cells of the maxilla-mandibular junction and later in the progenitor cells and undifferentiated chondrocytes of the condyle as well as the glenoid fossa of the developing TMJ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
94
0
3

Year Published

2009
2009
2015
2015

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 64 publications
(103 citation statements)
references
References 47 publications
6
94
0
3
Order By: Relevance
“…In mice, ablation of Shox2 causes embryonic lethality at midgestation due to cardiac and vascular defects (11). Studies of Shox2-null and conditional knockout mice have shown an indispensable role of Shox2 in the formation of the proximal portion of the limb skeleton and synovial joints (12,13). The shortened limbs observed in Turner syndrome may be related to loss of SHOX (14,15).…”
mentioning
confidence: 99%
“…In mice, ablation of Shox2 causes embryonic lethality at midgestation due to cardiac and vascular defects (11). Studies of Shox2-null and conditional knockout mice have shown an indispensable role of Shox2 in the formation of the proximal portion of the limb skeleton and synovial joints (12,13). The shortened limbs observed in Turner syndrome may be related to loss of SHOX (14,15).…”
mentioning
confidence: 99%
“…1, upper right) (18,19). One key gene previously noted to be expressed during and function within the growth plate of the condylar cartilage is Indian hedgehog (Ihh) (20)(21)(22). Ihh has been studied extensively during endochondral ossification of the long bones, where it plays several distinct roles.…”
mentioning
confidence: 99%
“…Most obviously, mouse embryos nullizygous for Shox2 die between E11.5 and E17.5 due to aberrant formation of the sinoatrial node (Blaschke et al, 2007;Espinoza-Lewis et al, 2009;Yu et al, 2007). Shox2 mutants also exhibit a unique incomplete clefting phenotype of the future hard palate (Yu et al, 2005), as well as defects in temporomandibular joint formation (Gu et al, 2008) and in the differentiation of Ntrk2-positive dorsal root ganglion mechanosensory neurons (Scott et al, 2011). Finally, loss of Shox2 function in embryonic limb mesenchyme causes significant neural and muscular patterning defects in the forelimb stylopod (Vickerman et al, 2011), in addition to severe rhizomelia (Cobb et al, 2006;Yu et al, 2007).…”
Section: Discussionmentioning
confidence: 99%